Analisis Kemampuan Komunikasi Matematis pada Materi Bentuk Aljabar Kelas VII SMP N 1 Utan - Muzaki, Ahmad; Yulianti, Sri (Jurnal Ilmiah IKIP Mataram, 2023)
ThisÂ study Â aimsÂ to Â determine Â the Â mathematical Â communication Â skillsÂ in Â the Â material Â of algebraic forms of seventh grade students of SMP Neri 1 Utan. The subjects of this study were students of class VII.1 SMP Negeri 1 Utan, totaling 16 people. The method used is descriptive with a qualitative approach. Â The dataÂ collection technique usedÂ inÂ this study Â was Â writingÂ consistingÂ of Â 5Â description questions, and interview sheets needed to obtain support data. The tests were conducted to determine students’ mathematical communication skills when working on questions, while interviews were used to obtain more in-depth information about students’ written mathematical communication skills. The results showed that students’ mathematical communication skills in the high category 25% of students were able to achieve allÂ indicators of Â written mathematicalÂ communicationÂ skills, Â while the mediumÂ category 56.25% Â were able Â toÂ meet Â 2Â indicators of Â written mathematicalÂ communicationÂ skills and Â the Â low category 18.75% low were able to meet 1-2 indicators of written mathematics communication skills.